Determinants of Financial Performance and Their Implications for Corporate Values - Matdio Siahaan; Hari Gursida; Hendro Sasongko (Dinasti Publisher, 2025)
The company has a goal of improving the welfare of shareholders by obtaining high company value which is measured through various aspects including the company's stock price which can reflect the overall investor assessment of each equity owned. If the stock price increases, the company's value will also increase. This study aims to determine the effect of capital structure, company size, managerial ownership and institutional ownership on company value which is proxied by price to book value (PBV) with financial performance on profitability which is proxied by return on assets (ROA) as an intervening variable. This study was conducted to analyze the determinants of Financial Performance and Company Value, namely Capital Structure, Company Size, Managerial Ownership and Institutional Ownership. The sample selection method uses the purposive sampling method, with the number of companies used as samples in this study as many as 12 companies, namely automotive and component sub-sector companies with an observation period of five years, so that the total observation data is 60. The research method used is a mixed research method between quantitative and qualitative. The regression results show that for 2019-2023, capital structure (-2.745), company size (-0.151), managerial ownership (-0.325), institutional ownership (0.564) have a significant effect on Financial Performance. Capital Structure (0.787), Managerial Ownership (-0;364) and Institutional Ownership (0.461) and Financial Performance (0.995) have a significant effect while Company Size (0.015) does not have a significant effect on Company Value.